Analisis Kemampuan Literasi Sains Siswa SMP dalam Pembelajaran Li-Pro-GP sebagai Alternatif menuju SGDs Pendidikan - Yuni Pantiwati; Tasya Novian Indah Sari; Andri Rudi Yanto (Universitas Sebelas Maret, 2025)
One of the goals of the SDGs is quality education, ensures that all groups have good literacy and numeracy skills. Efforts made include implementing learning models that accustom students to literacy, Li-Pro-GP learning model. The purpose of the study was to analyze the scientific literacy skills of JHS students in the application of the Li-Pro-GP learning model to support the Education SDGs. The type of research is a pre-experimental design, a one-group posttest-only design. The study was conducted in August 2024 at a private JHS in Malang City. The research population was 43 students and the sample was 43 students using a saturated sampling technique. The technique of collecting data is done through tests and non-tests. Data collection instruments were essay questions and self-assessment questionnaires. Scientific literacy ability data were analyzed descriptively to determine the achievement of scientific literacy indicators. The results of the study showed that the ability of science literacy in the context aspect was 72% (good), competence 76% (good), knowledge 79% (good), and attitude 77% (good). The Li-Pro-GP learning model can be used as an alternative to support the SDGs of education because, in its implementation this model accustoms students always to be literate and integrates character-building.